Effect of whole-body vibration training with two different vibration amplitudes on lower limb performance - Haleva, Y.; Dunsky, A.; Rubinstein, M.; Kleinöder, H.; Mester, J. (German Journal of Exercise and Sport Research, 2023)
Whole-body vibration (WBV) systems are increasingly used among athletes, yet the literature lacks input on differences in impact following high or low amplitudes. The purpose of this study was to examine the effect of a 4-week WBV training at high or low amplitudes, with external loads, on maximal isometric strength, muscular endurance, and different performances of vertical jump. In all, 24 physical education undergraduate students were randomly allocated to a high (4mm amplitude) or low (2mm amplitude) vibration group. The study included pretest assessments, 4-week intervention phase with three weekly training sessions, and posttest assessments. During the 12 intervention sessions, participants performed six sets of 30s leg-dynamic back squats with external load of 40% of one repetition maximum. Assessments included maximal isometric muscle strength, muscular endurance, squat jump, counter-movement jump, and drop jump. Statistical analysis was done using two-way analysis of variance (ANOVA) with group × time (2 × 2) as a model factor. The results revealed no significant groups × time interactions in any test. However, significant improvements were found in all measures among the high amplitude vibration group: maximal isometric muscle strength (p< 0.05), squat jump (p< 0.01), counter-movement jump (p< 0.01), drop jump (p< 0.01), and muscular endurance (p< 0.01), following the intervention, yet in only three variables: squat jump (p< 0.01), counter-movement jump (p< 0.01), and drop jump (p< 0.05) among the low amplitude vibration group. Based on the current results, we conclude that while high amplitude WBV training in physical education students could enhance muscular strength and endurance as well as jumping performances, low amplitude WBV protocols may improve only jumping performances.